Nickel aluminum layered double oxides modified magnetic biochar from waste corncob for efficient removal of acridine orange. (November 2020) - Wang, Huan; Zhao, Wei; Chen, Youning; Li, Yuhong
Graphical abstract: Highlights: MC1 /NiAl-LDO from corncob was prepared by the pyrolysis of MC1 /NiAl-LDH. The surface area of MC1 /NiAl-LDO is much higher than that of MC1. MC1 /NiAl-LDO for AO is higher adsorption capacity than MC1 . MC1 /NiAl-LDO can be used for nine times. Abstract: The objective of this work was to use corncob as raw material to prepare green reusable magnetic biochar for removal of dyes in wastewater. For this purpose, an environmentally friendly NiAl layered double oxides modified magnetic corncob biochar (MC1 /NiAl-LDO) was obtained by pyrolysis of NiAl layered double hydroxides modified magnetic corncob biochar (MC1 /NiAl-LDH) at 700 °C for 3 h. The surface area of MC1 /NiAl-LDO is 552.62 m 2 ·g −1, which was much higher than that of MC1 (26.83 m 2 ·g −1 ). MC1 /NiAl-LDO for acridine orange (AO) exhibited higher adsorption ability, the adsorption capacity of MC1 /NiAl-LDO was increased by 90% compared with MC1 . Adsorption experiments for AO on MC1 /NiAl-LDO were carried with effect of pH, adsorption time, initial concentrations of AO and ionic strength. MC1 /NiAl-LDO can be recycled nine times. The results exhibited that MC1 /NiAl-LDO was a low cost adsorbent, providing good example for th agricultural waste recycling.